Levelling-up national economies through regional development? a panel fsQCA approach applied to Great Britain - David Pickernell (The Annals of Regional Science, 2025)
There is currently renewed policy focus on ‘levelling-up’ economic performance across Great Britain’s regions and nations. Heterogeneous historical regional economic experiences lead to questions over the need for policy differences and trade-offs, and roles of regional, versus national level, policies in the longer term. This paper examines, using panel fuzzy-set Qualitative Comparative Analysis (fsQCA), combinations of education and human capital, entrepreneurship, and economic activity conditions driving economic development differences across local authorities in Great Britain. Analysis identifies three and six condition-based pathways for presence and absence of high local economic development (LED) respectively, absence pathways having a particular geographic focus. This identifies different sets of regions, where disadvantage is “deep-rooted” (and non-traditional policymaking is needed), advantage is long-established, or where policy is most likely to make a positive difference. It also identifies a need to tailor policy according to the pathway(s), rather than assuming homogeneous approaches are appropriate. Finally, exemplar regions offer case studies of how future policy can assist movement from absence to presence of high LED.